INTENSITAS KERJA PENGAWAS PERIKANAN PADA AKTIVITAS PATROLI LAUT PENGAWASAN SUMBERDAYA KELAUTAN DAN PERIKANAN DI JAKARTA - Singgih Prihadi Aji; Budi Hascaryo Iskandar; Fis Purwangka (Jurnal Teknologi Perikanan dan Kelautan, 2016)
FAO (2010) mentioned that fishing is one of the most dangerous jobs in the world. Surveillance against fishing in the sea is part of the management of fisheries is also the one job that has the potential of high danger. The number of accidents was compiled by the National Disaster Mitigation Agency (BNPB) of Indonesia between the years 2011- 2014 i.e. 80 events that comprise the crash land, sea and air. Than 80 accidents, as many as 55 events is an accident at sea involving ship of various types which include commerce ship, cargo ship, fishing boats, ship/boat belonging to the government and other vessels. It is important to study the safety of the ship’s crew to know the hazard and risk in each element involved in the surveillance patrol SDKP at sea. The purpose of this research is to identify activities and know the intensity of the fisheries inspector work on marine and fisheries patrols by using speedboat which can potentially cause the occurrence of accidents at sea. The method of this research is a descriptive numeric. Data analyzed by identifying the activity with the Hierarchical Task Analysis (HTA). The result showed that the sea surveillance patrol SDKP activity at sea is 5 stages with a total of 84 activities. The number of the crew of the patrol ship as many as 12 people with the biggest responsibility is fisheries surveillance. The intensity of the total work on sea surveillance patrol SDKP namely 244 OA (people activity), which mean that in carrying out supervisory patrol SDKP from the early stages up to the end of the work requires effort of cruise activity and surveillance at sea is a sea patrol sub goal of the SDKP supervision has the potential risk of an accident the greatest work due to the high work intensity.